Suicide in Canada: Is Poisoning Misclassification an Issue?. (July 2016) - Skinner, Robin; McFaull, Steven; Rhodes, Anne E.; Bowes, Matthew; Rockett, Ian R. H.
Objective: The aim of this study is to compare Canadian suicide rates with other external causes of death to examine potential poisoning misclassifications as a contributor to suicide underreporting. Method: The study used Statistics Canada mortality data from 2000 to 2011 to calculate sex-and age-specific ratios by external cause of injury codes. Results: The overall Canadian suicide rate, as well as the poisoning suicide rate, declined over the study timeframe by an average annual percentage change (AAPC) of 1.0% each year. However, unintentional and undetermined poisonings increased significantly during the timeframe. Unintentional poisoning mortality (primarily narcotics and hallucinogens, including opioids) increased in proportion to suicides for both sexes, although females were consistently higher. The undetermined death to suicide ratio was higher and increasing for females. Poisonings of undetermined intent increased over time to comprise 47% to 80% of the undetermined death category for males and females combined. Conclusions: Canadian poisoning suicide rates declined, in contrast to rising unintentional and undetermined poisoning mortality rates. This trend is similar to that of the United States, supporting the hypothesis that misclassification of poisoning deaths may also be an issue in Canada.